A Resolução de Problemas e o Estudo de Gráficos: uma proposta para a construção do conceito de função com auxílio das TIC - Ri, Mariana Lopes Dal (2015)
The following research aims at the problem solving and the study of graphics, combined with the use of Information and Communication Technologies (ICT), as helpful tools while working in classroom. The subjects involved are junior students of professional high school, who performed, in classroom and computer labs, a learning sequence drawn up by the teacher in order to investigate the contributions of the math Learning-Teaching-Assessment (LTA) by problem solving, to introduce the concept of function from its graphics. The instruments used were online questionnaires and resolutions, prepared by the own students with pencil and paper and, later, aided by spreadsheet. Reports and observations, which occurred during the development of the employed methodology, also contributed to the analysis and interpretation of the results. In the findings were possible to see that the students had identified themselves and joined the innovative classes, which uses the ICT. The resolutions of the questions with spreadsheet were more effective and dynamic than the ones with pencil and paper, once they were graphic’s handling activities. On the other hand, the key point of the methodology are the moments identified as "plenary" and "search for consensus", when the students, who effectively solved the activities, could place their views and doubts, so that, together, everyone involved could reach a consensus, for the subsequent formalization of the content from the constructions carried out in class. The preparation of graphics in spreadsheets contributed for the comprehension of the function concept, and the methodology of the LTA through problem solving has increased the learning process as it offered a different way of conceiving it other than the one the students were used to, what looked like harder. For this process, nevertheless, there was a greater involvement from the students in the question resolution and in the understanding of the function concept.